Case Study of the Implementation of the Use of the Pijar School Application as an Educational Technology in the Double System Partnership Program (PDS) at State of Senior High School (SMAN) 18 Garut - Santi Susanti; Nizar Alam Hamdani; Asep Nurjamin (Jurnal Locus Penelitian dan Pengabdian, 2026)
The digital transformation of education necessitates the integration of technology into learning processes. However, a gap persists between the potential of digital platforms and their effective implementation in partnership-based programs. This study aims to analyze the implementation of the Pijar Sekolah application as an educational technology to support the Partnership Double System (PDS) program at SMAN 18 Garut, focusing on its effectiveness, challenges, and optimization strategies. A qualitative approach with a case study design was employed. Data collection techniques included observation, in-depth interviews with the principal, teachers, and students, as well as documentation. The findings reveal that while Pijar Sekolah has the potential to improve learning effectiveness, strengthen school-industry collaboration, and support an integrated evaluation system, its implementation is suboptimal. Key obstacles include limited infrastructure, low digital literacy among users, resistance to change, and a lack of systematic integration with industry partners. The use of the platform remains predominantly administrative rather than pedagogical. This study concludes that the success of educational technology in a PDS context depends not only on platform availability but also on human resource competence, institutional support, and strategic integration. The implications suggest a need for targeted training, infrastructure improvement, and a systematic integration framework for school-industry partnerships.